Strong-interface dual-connection carbon fiber epoxy resin composite material and preparation method thereof

By using PVA-g-PHEA as a sizing agent, the carbon fiber is surface treated to form a strong interface dual-connection structure, which solves the problem of poor interface adhesion between carbon fiber and polymer, and significantly improves the mechanical properties and weaving quality of the composite material.

CN119661877APending Publication Date: 2025-03-21ANHUI POLYTECHNIC UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411602845.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

Poor interface adhesion between carbon fiber and polymer leads to a decrease in mechanical properties of carbon fiber reinforced composite materials, and carbon fibers are prone to bleaching during warp weaving, affecting weaving quality.

Method used

PVA-g-PHEA is used as a sizing agent to surface the carbon fiber, improve its interface compatibility and binding force with epoxy resin, and form a strong interface dual-connection structure through grafting reaction and sizing technology.

Benefits of technology

The tensile strength, bending strength and shear strength of carbon fiber epoxy resin-based composite materials have been significantly improved, and the interface adhesion and weaving quality have been improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119661877A_ABST
    Figure CN119661877A_ABST
Patent Text Reader

Abstract

The invention discloses a strong-interface dual-connection carbon fiber epoxy resin composite material and a preparation method thereof.The preparation method of the composite material comprises the following steps that S1, hydroxyethyl acrylate serves as a grafting monomer, ammonium ferrous sulfate and hydrogen peroxide serve as initiators to conduct grafting reaction on PVA, and PVA-g-PHEA is prepared; s2, carbon fibers subjected to desizing treatment are soaked in PVA-g-PHEA slurry for sizing, then the sized carbon fibers serve as a reinforcement body, epoxy resin serves as a matrix, forming is conducted, and the strong-interface double-connection carbon fiber epoxy resin composite material is prepared. According to the invention, the combination effect between the carbon fiber and the epoxy resin can be obviously improved, so that the performance of the strong-interface dual-connection carbon fiber epoxy resin composite material is obviously improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of textile technology, and in particular to a strong-interface double-connected carbon fiber epoxy resin composite material and a preparation method thereof. Background Art

[0002] Carbon fiber is a special fiber material with a carbon content of more than 90%, which is made of graphite chips stacked along the fiber axis. Carbon fiber has excellent mechanical properties. As a composite material reinforcement, it gives carbon fiber reinforced composite materials higher specific strength, wear resistance, specific modulus and other excellent properties than traditional materials. It has attracted the attention of many scholars and has been widely used in aerospace, chemical industry and other fields. In recent years, the global market demand for carbon fiber has shown an increasing trend year by year. At present, global carbon fiber production is mainly concentrated in Japan, the United States and Europe. The research and development of carbon fiber products in my country is mainly concentrated on polyacrylonitrile-based carbon fiber. With the advancement of technology and the steady progress of industrialization, the performance of some carbon fiber products developed by my country has reached the level of similar foreign products, which has driven the rapid development of my country's polyacrylonitrile-based carbon fiber industry.

[0003] As we all know, carbon fiber is very brittle and chemically inert. There are many problems in the process of using it to prepare carbon fiber reinforced composite materials, such as fiber breakage, fuzzing, and weak adhesion between fiber and matrix. In addition, the chemical inertness of the carbon fiber surface, the few active functional groups, and the poor wettability between the carbon fiber and the polymer (such as resin) result in poor interfacial adhesion between the two. The interface becomes the weak link of the composite material, resulting in reduced mechanical properties of carbon fiber reinforced composite materials. Therefore, in the process of developing carbon fiber composite materials, the means or methods that can improve the interfacial adhesion behavior between carbon fiber and polymer have received extensive attention from scholars. In addition, when carbon fiber tows or carbon fiber yarns are used as warp yarns for weaving, repeated mechanical actions such as stretching and bending will cause the carbon fiber to have problems such as fuzzing, resulting in unclear openings, which will lead to the inability to weave smoothly.

[0004] In view of the above problems, fiber surface sizing technology is an important means to effectively solve this problem during the production and use of carbon fiber. In order to obtain a good sizing effect, enhance the interface between carbon fiber and resin matrix while protecting carbon fiber, the development of high-performance and efficient sizing agents has important significance and commercial prospects. Summary of the invention

[0005] Based on the technical problems existing in the background technology, the present invention proposes a strong interface double-connected carbon fiber epoxy resin composite material and a preparation method thereof, which can significantly improve the bonding effect between carbon fiber and epoxy resin, thereby significantly improving the performance of the carbon fiber epoxy resin-based composite material.

[0006] The preparation method of the strong interface double-connected carbon fiber epoxy resin composite material proposed by the present invention comprises the following steps: S1: Preparation of PVA-g-PHEA PVA-g-PHEA was prepared by grafting PVA with hydroxyethyl acrylate as grafting monomer and ammonium ferrous sulfate and hydrogen peroxide as initiators. S2: Preparation of carbon fiber epoxy resin based composites The desized carbon fiber is immersed in a PVA-g-PHEA slurry for sizing, and then the sized carbon fiber is used as a reinforcement and the epoxy resin is used as a matrix for molding to obtain a carbon fiber epoxy resin-based composite material.

[0007] Preferably, the mass ratio of PVA, hydroxyethyl acrylate, ammonium ferrous sulfate and hydrogen peroxide in S1 is 120:5-20:0.12-0.2:0.26-0.43.

[0008] Preferably, the PVA in S1 is one or more of PVA1799, PVA1788, PVA0588, and PVA0599.

[0009] Preferably, the grafting reaction temperature in S1 is 30-45° C. and the time is 2-5 h.

[0010] Preferably, the mass fraction of the PVA-g-PHEA slurry in S2 is 0.15-1.0%.

[0011] Preferably, the sizing rate of the carbon fiber in S2 is 0.5-1.5%.

[0012] The invention provides a carbon fiber epoxy resin composite material with strong interface and double connection prepared by the method.

[0013] Beneficial technical effects of the present invention: The sizing agent of the present invention is used to treat the surface of carbon fiber and then combined with epoxy resin to prepare a carbon fiber epoxy resin-based composite material, which is significantly improved in tensile strength, bending strength and shear strength. This is because after the sizing agent of the present invention is sized on the surface of the carbon fiber, on the one hand, the sizing agent of the present invention has a good wetting and spreading effect on both the carbon fiber and the epoxy resin surface, then the epoxy resin must also have a good wetting and spreading effect on the carbon fiber surface sized by the sizing agent of the present invention, so that the sizing agent behaves like a "bridge" between the carbon fiber and the resin, and achieves a strong double connection between the carbon fiber and the epoxy resin, so that a strong interface effect is generated between the carbon fiber and the epoxy resin, and the two are firmly connected together; on the other hand, the PVA grafted material formed on the carbon fiber surface replaces the inert carbon fiber surface, and the functional groups on the PVA grafted material can generate binding force with the functional groups in the epoxy resin matrix, and good compatibility is generated between the two. At the same time, the PHEA grafted side chain in the PVA grafted material on the carbon fiber surface can extend into the epoxy resin, entangle with the epoxy resin molecular chain, and form a diffusion layer. The hydroxyl groups in the grafted side chain combine with the hydroxyl groups in the epoxy resin to form hydrogen bonds and react with the epoxy groups to form a strong bond, which also promotes the formation of a strong interface; thereby significantly improving the performance of the composite material. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 The infrared spectrum of the sample proposed by the present invention; Figure 2 XRD diagram of the sample proposed in the present invention; Figure 3 Microscope images of (a) PVA and (b) PVA-g-PHEA proposed in the present invention; Figure 4 SEM images of (a) CF (original), (b) CF (retrograde), and (c) CF (modified) proposed in the present invention; Figure 5 (a) tensile strength and (b) tensile stress-strain curve of the composite material proposed in the present invention; Figure 6 The tensile fracture damage morphology images of (a) CFERC (retrograde), (b) CFERC (original), (c) CFERC (modified) and the tensile cross-sectional SEM images of (d) CFERC (retrograde), (e) CFERC (original), (f) CFERC (modified) proposed in the present invention; Figure 7 (a) flexural strength and (b) flexural stress-strain curve of the composite material proposed in the present invention; Figure 8Bending fracture damage morphology images of (a) CFERC (retracted), (b) CFERC (original), (c) CFERC (modified) and bending cross-sectional SEM images of (d) CFERC (retracted), (e) CFERC (original), (f) CFERC (modified) proposed in the present invention; Fig. 9 (a) shear strength and (b) shear stress-strain curve of the composite material proposed in the present invention; Fig.10 The morphological diagrams of the CFERC (original) and CFERC (modified) after shear damage proposed in the present invention. DETAILED DESCRIPTION

[0015] The present invention will be further explained below in conjunction with specific embodiments.

[0016] Example The preparation method of the strong interface double-connected carbon fiber epoxy resin composite material proposed by the present invention comprises the following steps: S1: Preparation of PVA-g-PHEA Weigh the PVA1799, PVA1788, PVA0588 and PVA0599 samples (dry weight 120g) that have been fully crushed by a powder grinder and further fully ground using a mortar into a container, and transfer 28g of the prepared 0.5% (mass fraction) ammonium ferrous sulfate solution, 30g of a 1.0% (mass fraction) hydrogen peroxide aqueous solution and 10g of the grafting monomer hydroxyethyl acrylate (HEA) into a spray bottle, and spray them evenly on the PVA sample while stirring. During the spraying process, first spray 2 / 3 of the above-mentioned initiator amount and all of the HEA evenly at the same time, then continue to spray the remaining 1 / 3 of the initiator and continue to stir, and the spraying is completed within 30 minutes. After the spraying is completed, continue the reaction at 40°C for 3.5 hours, and ensure that the product is turned over every half an hour. After the reaction, it was redispersed with anhydrous ethanol, and the product was filtered and washed three times, and then dried in an oven at 45°C, and then crushed and sieved to obtain PVA- g -PHEA sample. PHEA is the abbreviation of poly(HEA), which is polyhydroxyethyl acrylate.

[0017] S2: Preparation of strong interface double-connected carbon fiber epoxy resin composites Carbon fiber desizing: After treating the carbon fiber with acetone in an ultrasonic cleaner for a sufficient time, wash it with distilled water until there is no odor to ensure that the surface of the carbon fiber is clean. Finally, place the cleaned carbon fiber in an oven at a temperature of 100°C for drying.

[0018] Carbon fiber sizing: Weigh 3 g of PVA prepared by S1 g-PHEA sample, add distilled water to make a dispersion with a mass fraction of 0.3%, continue stirring (120r / min) and heat to 95℃. After keeping warm for a certain period of time, put the rectangular metal yarn frame wrapped with carbon fiber yarn into an iron box kept at 95℃ and immerse for 5 minutes. Take it out and dry it under constant temperature and humidity conditions. The weight of carbon fiber before and after sizing was weighed and the sizing rate was 1.0%, which can be compared with the original carbon fiber. Desized carbon fiber, original carbon fiber and PVA- g -PHEA sizing treated carbon fibers are named CF (de-sizing), CF (original) and CF (modified); g -PHEA, PVA1788- g -PHEA, PVA0588- g -PHEA, PVA0599- g The carbon fibers treated with -PHEA sizing were named CF(1799), CF(1788), CF(0588) and CF(0599), respectively.

[0019] Preparation of composite materials: Using carbon fiber as reinforcement, CFERC samples were prepared by injection molding. First, a homemade polytetrafluoroethylene plate with a thickness of 1.0 mm was used as the experimental mold, and CF (original) and CF (modified) were placed inside the mold, respectively. Then, epoxy resin was poured into the homemade mold containing the carbon fiber bundle, and CFERC was obtained after curing. The composite materials made of CF (retired), CF (original) and CF (modified) were named CFERC (retired), CFERC (original) and CFERC (modified); the composite materials made of CF (1799), CF (1788), CF (0588) and CF (0599) were named CFREC (1799), CFREC (1788), CFREC (0588) and CFREC (0599), respectively.

[0020] Take PVA0588 as an example. Figure 1 The infrared spectra of PVA0588 samples before and after grafting are shown in Figure 2. g -PHEA spectrum curve 1730cm -1 The peak intensity at 3300cm -1 The characteristic absorption peak of hydroxyl group at the location was also significantly enhanced, confirming that PHEA grafted side chains were successfully connected to the PVA0588 molecular chain.

[0021] Figure 2 Figure 2 is the XRD diagram of PVA0588 sample particles before and after grafting. gThe XRD curve of -PHEA is basically the same as that of PVA0588, with obvious characteristic diffraction peaks at diffraction angles of 19.4° and 40.5°, but the peak values ​​are slightly reduced. It is calculated that the crystallinity of PVA0588 is 24.3%, and PVA0588- g The crystallinity of the -PHEA sample was 22.2%, indicating that the introduction of PHEA could effectively reduce the crystalline structure of PVA0588 and reduce its crystallinity.

[0022] Figure 3 For PVA and PVA- g -PHEA particles under microscope. As can be seen from the figure, the PVA particles before grafting have a smooth surface and a variety of sizes ( Figure 3 a); PVA after grafting g -PHEA still maintains the morphological characteristics of particles and different sizes ( Figure 3 b).

[0023] Figure 4 The SEM images of CF (original), CF (retreated) and CF (modified) are shown. It can be seen that after the PVA-g-PHEA sizing treatment, the grooves on the surface of the single fiber have disappeared, and a polymer film composed of PVA-g-PHEA is attached to the surface, which also reflects the sizing effect of PVA-g-PHEA.

[0024] The present invention tests the tensile properties of the composite material on a WDW-20 microcomputer-controlled electronic universal testing machine according to the ASTM D638 standard, the tensile speed is 2 mm / min, and 5 valid data samples are tested; the testing method of the bending performance is as follows: according to the ASTM D790 standard, a 3-point bending test is performed on the composite material, the loading speed is set to 1 mm / min, the span-to-thickness ratio is 32:1, and 5 valid data samples are tested; according to the ASTM D5379 / D5379M-05 standard, the shearing properties of the composite material sample are tested on a special composite material testing machine, the loading speed is set to 1 mm / min, and 5 valid data samples are tested.

[0025] Figure 5 is the tensile strength test result of the composite material. Figure 5 As shown in (b), the tensile strength of CFERC (modified) has been improved. The smallest increase is in CFERC (0599), with a tensile strength of 81.2 MPa, an increase of 18.9% over CFERC (original); the largest increase is in CFERC (1799), with a tensile strength of 86.5 MPa, an increase of 26.6% over CFERC (original). The significant increase in tensile strength may be due to the PVA- g-The functional groups on the PHEA film generate a bonding force with the epoxy resin matrix. The bonding force allows the load applied to the resin matrix to be more effectively transferred to the carbon fiber, so that there is a good interface between the carbon fiber and the resin matrix, and the composite material exhibits better tensile properties.

[0026] Figure 5 (b) is the tensile stress-strain curve of CFERC. As can be seen from the figure, the tensile fracture of CFERC (original) is brittle fracture, while CFERC (modified) is still brittle fracture, but its stress and strain are greater than CFERC (original). The tensile strain of CFERC (1799) is 46.0% higher than that of CFERC (original), and the smallest CFERC (0599) has also increased by 15.5%. This also shows that in addition to the interfacial bonding between carbon fiber and epoxy resin matrix affecting the tensile properties of CFERC, the transition effect of the sizing layer also has a positive effect on improving the mechanical properties of the composite material. PVA- g -PHEA has a variety of functional groups, which can connect incompatible carbon fibers with epoxy resin matrix to form a strong interface phase, thereby improving the mechanical properties of the composite material.

[0027] Taking CFERC (1799) as a comparative example, the tensile fracture surface of the CFERC sample was analyzed. Figure 6 (ac) are the tensile fracture morphologies of CFERC under an optical microscope. As can be seen from the figure, there are obvious cracks on the tensile section of CFERC (retreat), and the tensile fracture is uneven and tooth-shaped ( Figure 6 a); CFERC (original) has been sizing treated, and its fracture is slightly neater than CFERC (retarded) ( Figure 6 b); The tensile fracture surface of CFERC (1799) showed no cracks under an optical microscope, and the tensile fracture surface was relatively neat ( Figure 6 c). In addition, it can be seen that there is fiber extraction at the fracture of CFERC (retreat) and CFERC (original), but the extracted carbon fibers are poorly bonded to the resin matrix; while there is a large amount of resin residue at the fracture of CFERC (1799), and no obvious cracks or extraction marks are found, which also shows that PVA- g -The use of PHEA sizing agent improves the interfacial bonding between carbon fiber and epoxy resin.

[0028] In order to further characterize the tensile damage of CFERC samples, the SEM morphology of the tensile cross section of CFERC samples was characterized, such as Figure 6 As shown in (df). It can be seen that in the tensile fracture sections of CFERC (retrograde) and CFERC (original), there are obvious pores between the carbon fiber and the resin, and the pores are relatively large ( Figure 6 d. Figure 6e). In addition, the carbon fiber was pulled out, the fiber was broken, and the resin matrix was debonded. There was no resin adhesion on the surface of the carbon fiber stretched out from the matrix. This shows that the interface bonding between CF (de-bonded) and CF (original) and the epoxy resin matrix is ​​poor. This poor bonding will lead to a decrease in the mechanical properties of CFERC. In the tensile fracture section of CFERC (1799), no obvious pores were found between the carbon fiber and the resin matrix, and the interface bonding between the carbon fiber and the matrix was better ( Figure 6 f). In addition, the fewer carbon stretched fibers, the shorter the broken fibers, the resin matrix adheres to the surface of the stretched fibers, the smaller the gap between the fibers and the matrix, and the better the interface bonding effect.

[0029] Figure 7 The bending strength test results of the composite material. Figure 7 (a) It can be seen that compared with the flexural fracture strength of 104MPa of the CFERC (original) sample, the flexural fracture strength of the CFERC (modified) sample (124MPa~131MPa) has been enhanced. The maximum increase in flexural strength is 26.0%, and the minimum increase is 19.2%. g -The various functional groups on PHEA can produce various forces with the functional groups on the epoxy resin molecules, thereby enhancing the bonding effect between carbon fiber and epoxy resin and forming a strong interface phase between the two. This may be an important reason why CFERC (modified) has higher bending resistance than CFERC (original).

[0030] Figure 7 (b) shows the bending stress-strain curve of the CFERC sample. As can be seen from the figure, compared with the CFERC (original) sample, the bending stress-strain of the CFERC (modified) is significantly increased, indicating that PVA- g -PHEA sizing treatment of carbon fiber is of great significance to improving the toughness of CFERC and increasing the damage tolerance of CFERC. When CFERC (original) reaches the bending load stress limit, it will show obvious brittle fracture due to the influence of bending load. In contrast, CFERC (modified) continues to deform during the loading process. When it reaches the maximum bending load limit, although it is still brittle fracture, its stress and strain are greatly improved compared with CFERC (original). The reason may be due to PVA- g -PHEA sizing agent has good compatibility with epoxy resin, which has a positive effect on the interface bonding between carbon fiber and resin matrix, making CFERC (modified) show excellent bending properties.

[0031] Taking CFERC (1799) as an example, the bending fracture surface of the CFERC sample was analyzed. Figure 8(ac) is the bending fracture morphology of CFERC under an optical microscope. It can be seen from the figure that there are obvious cracks on the bending section of CFERC (retreat), and the bending fracture is not neat ( Figure 8 a); CFERC (original) has been treated with sizing, and its fracture is slightly neater than that of CFERC (retarded) ( Figure 8 b); The bending section of CFERC (1799) has no cracks under an optical microscope, and the bending fracture is relatively neat ( Figure 8 c). In addition, it can be seen that there are obvious resin damage and microcracks on the bending damaged section of CFERC (1799), while there are no obvious microcracks on the bending sections of CFERC (retrograde) and CFERC (original). In addition, a large number of carbon fibers at the fracture of CFERC (retrograde) and CFERC (original) were pulled out from the resin matrix, and the surface of the pulled out carbon fibers was neat and smooth, and no obvious resin residue was found, which indicates that the interface bonding between the carbon fibers and the epoxy resin is poor. After CFERC (1799) was damaged by bending, there was obvious matrix resin residue on the surface of the carbon fibers and the cross section of the composite material. These confirm that sizing treatment can enhance the bonding between carbon fibers and the epoxy resin matrix, and that after PVA- g -PHEA sizing treatment forms a better interface bonding between carbon fiber and epoxy resin matrix, giving CFERC (modified) higher bending strength than CFERC (original).

[0032] SEM technology was used to further characterize the apparent morphology of the bending fracture cross-section of the CFERC sample. Figure 8 (de) are the SEM images of the bending fracture sections of CFERC (deformed), CFERC (original) and CFERC (1799) samples. It can be seen that in the bending fracture sections of CFERC (deformed) and CFERC (original), there are obvious pores between the carbon fiber and the resin, and the pores are relatively large ( Figure 8 a. Figure 8 b). The treated carbon fiber was broken at the cross section, indicating that PVA1799- g -PHEA is located between the carbon fiber and the resin matrix, forming an effective interface transition layer and improving the efficiency of stress transfer ( Figure 8 c). In the bending fracture section of CFERC (retracted), there are many gaps between the carbon fiber and the epoxy resin. The surface of the carbon fiber is not covered by the resin and peels off from the resin. The interface strength is relatively low and weak. In the bending fracture section of CFERC (1799), the carbon fiber is not peeled off from the resin to produce gaps at the interface. On the contrary, after the composite material is broken, the surface of the carbon fiber is covered with a large amount of epoxy resin, and the adjacent carbon fibers are integrated together by the resin matrix, so that the interface between the carbon fiber and the resin is effectively improved.

[0033] Fig. 9 is the shear strength result of the composite material. Fig. 9 As shown in (a), compared with CFERC (original), the shear strength of all CFERC (modified) is improved, indicating that this sizing treatment gives CFERC higher shear performance. This may be due to the poor bonding between the inert groups on the surface of the original carbon fiber and the epoxy resin matrix, while the PVA- g -PHEA sizing treatment has a sizing film layer on the surface of the carbon fiber that is well bonded to the resin matrix, which promotes the interface bonding between the two, thereby increasing the shear strength of the CFERC (modified) sample. In addition, it can be seen from the figure that compared with CFERC (original), the shear strength value of CFERC (1799) increased by 37.7%, and the shear strength of CFERC (0599), CFERC (0588) and CFERC (1788) increased by 15.1%, 17.2% and 32.1% respectively.

[0034] Fig. 9 (b) is the shear stress-strain curve of CFERC. CFERC (original) was the first to show crack damage, and the shear stress when the crack damage occurred was relatively small. CFERC (modified) not only had a delayed crack damage time, but also required a larger shear stress. As can be seen from the figure, the shear stress increase of CFERC (0599) was the smallest, and the shear stress increase of CFERC (1799) was the largest. This shows that PVA- g -PHEA sizing agent is beneficial to further improve the interfacial properties of CFERC, and PVA1799- g -PHEA has the most obvious effect. The reason is that the improvement of interfacial bonding strength is mainly due to the PVA- g -PHEA sizing agent is compatible with carbon fiber and resin, which can improve stress transfer efficiency and thus improve interface strength.

[0035] Fig.10 The following is a photo of the shear damage morphology of CFERC. As can be seen from the figure, the crack damage of CFERC (original) appeared at the edge interface of the carbon fiber and the epoxy resin. Although it was still transferred on the resin surface, it was accompanied by carbon fiber damage. Although the crack damage of CFERC (modified) also occurred at the root of the specimen notch, there was no carbon fiber damage. The reason may be that the interface bonding ability between CF (original) and the epoxy resin matrix is ​​weak, and cracks will appear at the contact edge of the carbon fiber and the resin under the action of an external load. When the crack reaches the interface after it is generated, it extends directly in the direction of the interface, causing debonding failure and the carbon fiber is damaged. The carbon fiber is subjected to PVA- g-After PHEA sizing treatment, the interfacial bonding performance between carbon fiber and resin matrix is ​​improved, which hinders the occurrence of cracks and changes the propagation direction of cracks. Therefore, CFERC has greater shear strength.

Claims

1. A method for preparing a strong interface double-connected carbon fiber epoxy resin composite material, characterized in that: The steps are as follows: S1: Preparation of PVA-g-PHEA PVA-g-PHEA was prepared by grafting PVA with hydroxyethyl acrylate as grafting monomer and ammonium ferrous sulfate and hydrogen peroxide as initiators. S2: Preparation of carbon fiber epoxy resin based composites The desized carbon fiber is immersed in a PVA-g-PHEA slurry for sizing, and then the sized carbon fiber is used as a reinforcement and the epoxy resin is used as a matrix for molding to obtain a carbon fiber epoxy resin-based composite material.

2. The method for preparing the strong interface double-connected carbon fiber epoxy resin composite material according to claim 1, characterized in that: The mass ratio of PVA, hydroxyethyl acrylate, ammonium ferrous sulfate and hydrogen peroxide in S1 is 120:5-20:0.12-0.2:0.26-0.

43.

3. The method for preparing the strong interface double-connected carbon fiber epoxy resin composite material according to claim 1, characterized in that: The PVA in S1 is one or more of PVA1799, PVA1788, PVA0588, and PVA0599.

4. The method for preparing the strong interface double-connected carbon fiber epoxy resin composite material according to claim 1, characterized in that: The temperature of the grafting reaction in S1 is 30-45°C and the time is 2-5h.

5. The method for preparing the strong interface double-connected carbon fiber epoxy resin composite material according to claim 1, characterized in that: The mass fraction of the PVA-g-PHEA slurry in S2 is 0.15-1.0%.

6. The method for preparing the strong interface double-connected carbon fiber epoxy resin composite material according to claim 1, characterized in that: The sizing rate of carbon fiber in S2 is 0.5-1.5%.

7. A strong interface double-connected carbon fiber epoxy resin composite material prepared by the method according to any one of claims 1 to 6.